Web-Based E-Procurement Development in Regional-Owned Enterprises (BUMD): An R&D Approach - Sutisna, Nandang; Abdul Rahman, Titik Khawa (Indonesian Scientific Journal, 2025)
This study presents the design, development, and evaluation of a web-based e-procurement system tailored to the institutional needs of a Regional-Owned Enterprise (BUMD), with a case implementation at PDAM Tirta Kahuripan. Employing a Research and Development (R&D) methodology and assessed using ISO/IEC 25010 standards, the system integrates six core procurement modules—e-Planning, e-Budgeting, e-Preparation, e-Sourcing, e-Contracting, and e-Inventory—alongside a Vendor Management System (VMS) to enhance procurement transparency and supplier accountability. System testing involved both quantitative and qualitative assessments. Functionality and reliability achieved perfect scores (100%), usability scored 79 based on a System Usability Scale (SUS) survey completed by 20 procurement personnel, and maintainability recorded a moderate index of 82.85 based on PHP Metrics analysis. Efficiency testing using GTMetrix resulted in a Grade C, indicating areas for performance optimization. These findings demonstrate that the system is both technically robust and operationally relevant, offering a replicable model for digital procurement reform in decentralized public institutions. The study contributes to interdisciplinary knowledge across software engineering, public sector management, and procurement governance, with implications for future integration, scalability, and policy adoption in similar institutional contexts.